Hubungan Bimbingan Belajar di Luar Sekolah dengan Tingkat Kecemasan Siswa-Siswi Kelas XII SMA Negeri 8 Solo dalam Menghadapi Ujian Nasional Tahun 2012 - Francine Roselind; Istar Yuliadi; Diffah Hanim (Nexus Pendidikan Kedokteran dan Kesehatan, 2013)
Background: High school students at final year commonly experience anxiety when preparing the National Examination. Many students will eventually take more intensive additional courses offered by other institutions outside their schools as part of efforts to anticipate disappointing results of the examination. This study aimed to seek the rela-tionship between attendance for intensive external course with anxiety degree among final year students of SMA Negeri 8 Solo preparing the 2012 National Examination. Methods: This cross-sectional study was conducted in March 2012 at SMA N 8 Solo. The 12th grade students were purposively sampled based on certain criteria. Subjects were asked to give informed consent and to complete a biodata form and T-MAS questionnaire which were administered 15 minutes before the classes dismissed. Data were analyzed using t-independent test. Results: This study showed that the anxiety scores of students taking and not taking external course differed significantly (t = -33,4; p<0,001). Students not attending an intensive external course were more anxious than their counterparts. Conclusions: Attendance for an intensive external course was related to anxiety among the 12th grade students of SMA N 8 Solo preparing the National Examination. Keywords: external course attendance, anxiety, high school national examination